2011
DOI: 10.1002/pro.616
|View full text |Cite
|
Sign up to set email alerts
|

An alternative view of the proposed alternative activities of hemopexin

Abstract: Hemopexin is a plasma protein that plays a well-established biological role in sequestering heme that is released into the plasma from hemoglobin and myoglobin as the result of intravascular or extravascular hemolysis as well as from skeletal muscle trauma or neuromuscular disease. In recent years, a variety of additional biological activities have been attributed to hemopexin, for example, hyaluronidase activity, serine protease activity, proinflammatory and anti-inflammatory activity as well as suppression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 129 publications
0
21
0
1
Order By: Relevance
“…84 At this point, it is unknown whether such non-heminrelated effects of Hpx are an inherent activity of the protein itself or if they are side effects caused by impurities or degradation products in some preparations of plasma-derived Hpx. 85 In mouse models of malaria, Hb/hemin-driven oxidative damage and NO depletion were linked to the evolution of cerebral malaria. 86 However, although we suspect that this pathophysiology could be attenuated by Hp and/or Hpx treatment, the efficacy of scavenger proteins has not yet been tested for this specific condition.…”
Section: The Role Of Hb Heme and Their Scavenger Proteins In Specifmentioning
confidence: 99%
“…84 At this point, it is unknown whether such non-heminrelated effects of Hpx are an inherent activity of the protein itself or if they are side effects caused by impurities or degradation products in some preparations of plasma-derived Hpx. 85 In mouse models of malaria, Hb/hemin-driven oxidative damage and NO depletion were linked to the evolution of cerebral malaria. 86 However, although we suspect that this pathophysiology could be attenuated by Hp and/or Hpx treatment, the efficacy of scavenger proteins has not yet been tested for this specific condition.…”
Section: The Role Of Hb Heme and Their Scavenger Proteins In Specifmentioning
confidence: 99%
“…Since a variety of different Hx preparations purified from plasma using different techniques were used in prior studies, it has not been possible to determine if the different results stem from differences in the purity or activity of Hxs and in particular if the reported effects on chemotaxis and protease activities are intrinsic to the Hx molecule or are contaminations of the purified molecules with plasma proteases (26). To address this issue, we compared protease activities of Hxs from different sources including those used in many of the above studies, and studied their effects on neutrophil chemotaxis in vitro and neutrophil migration in vivo.…”
Section: Amidolytic Assaymentioning
confidence: 99%
“…In this model, lethality was paradoxically increased in septic wild-type mice treated with the hemebinding protein, and reduced in Hpx-knockout animals (Spiller et al 2011). It was suggested that many of the reported nonheme-binding functions of Hpx were related to the experimental conditions or to impurities and degradation products in some experimental Hpx preparations (Mauk et al 2011); careful examination of such effects may be critical in the preclinical evaluation of Hpx-based therapeutics. Also, no comparative experimental data currently exist to determine which of the plasma-scavenging proteins within the Hb/heme-binding cascade might be the most protective against hemoglobin-driven pathologies.…”
Section: Scavenger Protein-based Therapeutics For Hemolytic Conditionsmentioning
confidence: 99%